2020
DOI: 10.1177/2325967120914932
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Double-Row Construct: An Untied Medial Row Demonstrates Equivalent Mean Contact Pressures in a Rotator Cuff Model

Abstract: Background: The merits of a double-row rotator cuff repair (RCR) construct are well-established for restoration of the footprint and lateral-row security. The theoretical benefit of leaving the medial row untied is to prevent damage to the rotator cuff by tissue strangulation, and the benefit of suture tape is a more even distribution of force across the repair site. These benefits, to our knowledge, have not been evaluated in the laboratory. Hypothesis: Leaving the medial row untied and using a suture bridge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Multiple laboratory studies showed no significant difference in contact pressures between untied and tied medial row. 14 , 15 However, we have observed increased gap formation on the articular side in knotless medial-row constructs, which is an unfavorable condition in tendon repairs. Gapping at the repair site also allows synovial fluid leakage to the footprint, which was previously proposed to be an unfavorable environment for tendon healing.…”
Section: Discussionmentioning
confidence: 89%
“…Multiple laboratory studies showed no significant difference in contact pressures between untied and tied medial row. 14 , 15 However, we have observed increased gap formation on the articular side in knotless medial-row constructs, which is an unfavorable condition in tendon repairs. Gapping at the repair site also allows synovial fluid leakage to the footprint, which was previously proposed to be an unfavorable environment for tendon healing.…”
Section: Discussionmentioning
confidence: 89%
“…Another 14 studies were excluded after a review of the full texts, and only 15 articles met all the eligibility criteria and were included for analysis (►Figure 1). [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Overall, inter-reviewer agreement regarding the final eligibility was excellent (there were no disagreements). These 15 studies were published in English from 2015 to 2020.…”
Section: Study Selection and Featuresmentioning
confidence: 89%
“…It is believed that preserving the structural integrity of the rotator cuff by avoiding knots in damaged tissues would improve healing. 33,34 Stone et al 31 measured the contact force and pressure at the tendon-footprint interface in a Sawbone (Vashon Island, WA, US) model graduated for biomechanical studies using an acellular human dermis allograft to simulate the rotator cuff tendon. The authors 31 compared a DR construct with a medial row with no knots to a medial row with knots, and found no significant differences.…”
Section: Biomechanics Of the Medial Row In Double Row Repairsmentioning
confidence: 99%